Crystal structure of dichloridobis(1,3-diisopropyl-4,5-dimethyl-2H-imidazole-2-thione-κS)zinc(II) - Flörke, Ulrich (Acta Crystallogr Sect E Struct Rep Online, 2014)
The molecular structure of the title compound, [ZnCl(2)(C(11)H(20)N(2)S)(2)], shows tetrahedral Zn coordination from two Cl ligands and two thione groups. The Zn—Cl bond lengths differ sligthly at 2.2310 (10) and 2.2396 (11) Å while the Zn—S bond lengths are equal at 2.3663 (9) and 2.3701 (10) Å. The Cl—Zn—Cl angle is 116.04 (4) and S—Zn—S is 101.98 (3)°. All other angles at the central Zn atom range from 108.108 (3) to 110.21 (4)°. The C—S—Zn angles are 100.75 (10) and 103.68 (11)°, the difference most probably resulting from packing effects, as both the C—S and both the S—Zn bonds are equal in each case. The two imidazole ring planes make a dihedral angle of 67.9 (1)°. The CH(3) groups of one isopropyl moiety are disordered over two sets of sites with occupation factors of 0.567 (15) and 0.433 (15). It may be noteworthy that the isomolecular Cu complex shows a different crystal packing (group–subgroup relation) with the Cu atom lying on a twofold rotation axis. In the crystal, the shortest non-bonding contact is a C—H⋯Cl interaction. This leads to the formation of centrosymmetric dimers that are stacked along the c-axis.